Tacrolimus-Based versus Cyclosporine-Based Immunosuppression in Hepatitis C Virus-Infected Patients after Liver Transplantation: A Meta-Analysis and Systematic Review - Liu, Zhenmin (Public Library of Science, 2014)
BACKGROUND: Most liver transplant recipients receive calcineurin inhibitors (CNIs), especially tacrolimus and cyclosporine, as immunosuppressant agents to prevent rejection. A controversy exists as to whether the outcomes of hepatitis C virus (HCV)-infected liver transplant patients differ based on the CNIs used. This meta-analysis compares the clinical outcomes of tacrolimus-based and cyclosporine-based immunosuppression, especially cases of HCV recurrence in liver transplant patients with end-stage liver disease caused by HCV infection. METHODS: Related articles were identified from the Cochrane Hepato-Biliary Group Controlled Trials Register, the Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library, Medline, and Embase. Meta-analyses were performed for the results of homogeneous studies. RESULTS: Nine randomized or quasi-randomized controlled trials were included. The total effect size of mortality (RR = 0.98, 95% CI: 0.77–1.25, P = 0.87) and graft loss (RR = 1.05, 95% CI: 0.83–1.33, P = 0.67) showed no significant difference between the two groups irrespective of duration of immunosuppressant therapy after liver transplantation. In addition, the HCV recurrence-induced mortality (RR = 1.11, 95% CI: 0.66–1.89, P = 0.69), graft loss (RR = 1.62, 95% CI: 0.64–4.07, P  = 0.31) and retransplantation (RR = 1.40, 95% CI: 0.48–4.09, P = 0.54), as well as available biopsies, confirmed that histological HCV recurrences (RR =  0.92, 95% CI: 0.71–1.19, P = 0.51) were similar. CONCLUSION: These results suggested no difference in posttransplant HCV recurrence-induced mortality, graft loss and retransplantation, as well as histological HCV recurrence in patients treated with tacrolimus-based and cyclosporine-based immunosuppresion.